2001
DOI: 10.1039/b101184g
|View full text |Cite
|
Sign up to set email alerts
|

Supported gold catalysts for CO oxidation: Effect of calcination on structure, adsorption and catalytic behaviour

Abstract: Adsorption behaviour and CO oxidation activity of and gold catalysts, prepared by TiO 2 -ZrO 2 -supported adsorption of gold colloids on the supports, have been investigated by pulse thermal analysis and di †use reÑectance FTIR spectroscopy. Structural investigations using transmission electron microscopy, X-ray di †raction and X-ray photoelectron spectroscopy showed that Au particles, mainly in the metallic state and with similar particle size distribution (2.0È3.0 nm), could be prepared on both supports, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 47 publications
8
72
0
4
Order By: Relevance
“…However, the similar turn over frequency found for the Au/TiO 2 and Au/MgAl 2 O 4 catalysts implies that such a support The absence of surface mediated oxygen transport in Au catalyzed CO oxidation is corroborated by isotope labeling studies of the CO oxidation reaction on Au/ TiO 2 and Au/Al 2 O 3 , which show that the CO 2 does not contain oxygen originating from the support [121]. Furthermore, the activities of a Au/TiO 2 , Au/Al 2 O 3 , Au/ZnO, and Au/ZrO 2 , catalysts do not follow the trend expected from the reducibility of the support [35,118,122]. A recent report of an active and stable LaPO 4 ) supported Au catalyst proves that non-oxidic supports can also be used [123], which further supports the idea that support-mediated oxygen transport does not necessarily contribute to the CO oxidation activity of Au catalysts.…”
Section: Influence Of the Supportmentioning
confidence: 51%
“…However, the similar turn over frequency found for the Au/TiO 2 and Au/MgAl 2 O 4 catalysts implies that such a support The absence of surface mediated oxygen transport in Au catalyzed CO oxidation is corroborated by isotope labeling studies of the CO oxidation reaction on Au/ TiO 2 and Au/Al 2 O 3 , which show that the CO 2 does not contain oxygen originating from the support [121]. Furthermore, the activities of a Au/TiO 2 , Au/Al 2 O 3 , Au/ZnO, and Au/ZrO 2 , catalysts do not follow the trend expected from the reducibility of the support [35,118,122]. A recent report of an active and stable LaPO 4 ) supported Au catalyst proves that non-oxidic supports can also be used [123], which further supports the idea that support-mediated oxygen transport does not necessarily contribute to the CO oxidation activity of Au catalysts.…”
Section: Influence Of the Supportmentioning
confidence: 51%
“…The result supports a Mars-van Krevelen mechanism, where lattice oxygen is involved in the oxidation process. 45,46 When gas-phase oxygen is present, formates and acetates are detected for TiO 2-Al 2 O 3 above 573 K, and for MnO x /TiO 2-Al 2 O 3 even at 473 and 573 K, and maleate species develop at 573 and 673 K. It is suggested that the oxidation of adsorbed chlorobenzene is enhanced due to the replenishment of lattice oxygen by gas-phase oxygen and MnO x is more active to the oxidation of adsorbed chlorobenzene.…”
Section: Discussionmentioning
confidence: 99%
“…8b, referring to the sample Au5, exhibits an additional high-frequency peak at 2117 cm À1 . Such peak is generally attributed to CO coordinated on neutral Au nanoparticles [34][35][36][37]. On the contrary, the assignment of the lowfrequency bands is quite controversial.…”
mentioning
confidence: 97%
“…The derived phases and their relative percentages along with the corresponding particles sizes are listed in Table 1. At time zero, large platinum particles of 13 nm are formed along with smaller (3 nm) gold enriched alloyed particles with average composition Au 65 Pt 35 . By letting the solution rest for 1 day before introducing silica, we observe the segregation of pure gold and pure platinum with average particle sizes of 7 nm and 5 nm, respectively.…”
Section: Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation